Pseudo-Cyril of Jerusalem on the life and the passion of Christ: a Coptic apocryphon - Broek, Roelof van den; Pseudo-Cyrillus (Vigiliae Christianae, 2013)
Front Matter -- The Manuscripts -- The Text: Sources, Apocryphal Elements, and Date -- On the Life and the Passion of Christ and the Other Coptic Homilies Attributed to Cyril of Jerusalem -- Appendices -- Bibliography -- Indexes.